USM-NCIA-CREST COOPERATION - A QUADRUPLE HELIX SUCCESS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PUTRAJAYA, 19 December 2016 Cooperation established that is based on the quadruple helix concept, combining the expertise from Universiti Sains Malaysia (USM) together with government agencies and the industry, including those from the Northern Corridor Implementation Authority (NCIA) and Collaborative Research in Engineering, Science and Technology (CREST) have been selected to be among the six finalists selected for the Prime Minister's Innovation Award (AIPM).